Health Physics and Radiological Health, 4th Edition. Issue 11 (23rd October 2013) - Pfeiffer, Douglas
Abstract : Health Physics and Radiological Health, 4th Edition. Johnson Thomas E., Birky Brian K., Lippincott Williams & Wilkins, a Walter Kluwer business, Baltimore, Maryland, 2012, 205.99. ISBN: 9781609134198, 1288 pp. (hardcover)